Urinary tract infection caused by Myroides spp. in diabetic patients: To be or not to be (Indian Journal of Case Reports, 2018)
Myroides is a non-fermentative, Gram-negative rod-like bacteria. It is a rare opportunistic pathogen which has been reported to cause many serious infections. Management of infections caused by Myroides can be challenging due to its high resistance to most antibiotics. We report three cases of urinary tract infection (UTI) due to Myroides species in patients with diabetes mellitus Type II. Myroides spp. isolated were resistant to all the antibiotics tested: Amoxicillin-clavulanic acid, piperacillin-tazobactam, cefepime, ceftriaxone-cefoperazone sulbactam, amikacin, gentamicin, imipenem, meropenem, ciprofloxacin, colistin, tigecycline, and co-trimoxazole. Two strains were sensitive to minocycline (minimum inhibitory concentration <1 ?g/mL). Two patients had Foley’s catheter in place and one patient had urinary retention at the time of diagnosis. The infection in two cases was nosocomial, whereas one case appeared to have a community-acquired infection with Myroides. Clinicians should consider the possibility of Myroides as a pathogen in UTI in diabetic patients, especially in nosocomial settings.